Improving marketing strategies of local rice in Ghanaian cities: A perspective from a survey of rice purchasers - Soullier, Guillaume; Sy, Mariam Maki; Agyei-Holmes, Andrew; Méndez del Villar, Patricio (CGIAR System Organization, 2025)
The advocacy of market-based approaches aims to enhance breeding and varietal adoption to meet final market demand. The CGIAR Market Intelligence Area of Work research emphasizes the role of downstream market actors in the process of varietal replacement and product substitution. This brief provides recommendations to breeders of local rice varieties and policymakers in order to support the development of local rice purchases. It characterizes the rice market segments in Ghana in terms of rice origins and quality attributes, describes the profile of purchasers in these segments, and identifies the drivers of rice preferences. A database of 1,214 rice purchasers was evaluated using descriptive analysis and econometric modeling. First, whereas varieties destined to Northern urban markets should be adapted to parboiling techniques and have a good swelling capacity and softness, the ones targeting cities in the Central and Southern regions should be perfumed and nutritious. Second, value chain actors should adopt technologies and practices to upgrade cleanliness and purity, which are reasons why urban consumers prefer imported rice over local rice. Third, the brief recommends differentiating local rice through branding strategies at the level of value chain actors or geographical areas. Local rice promotion campaigns can be carried out through traditional media, digital platforms, social relationships, and discovery tests, and can be tailored to cities. Finally, high-yielding varieties should be selected to increase local rice availability.